Noise level assessment in selected Nigerian plank industries: Bodija, Olorunsogo and Olunde in Ibadan, Oyo State, Nigeria (2018)
The nature of work that is commonly done in sawmills, together with the quantity of woods being worked on generate a lot of noise to the working environments. Noise is hazardous to human health as it can cause increased blood pressure, sleep deprivation and other physiological as well as psychological effects on the workers. The aim of this study was to assess the noise exposure level of sawmill workers to evaluate their safety at work. Three sawmills, all located in Ibadan, Oyo State, South-Western Nigeria were selected for study. Noise level measurements for planning, circular and drilling machines used in the three sawmills were determined using a precision sound pressure tester measurement. The fraction of exposure, and daily personal exposure levels for each of the machines were obtained. Also, questionnaires were administered to obtain subjective responses from the workers on their demographic data, their knowledge about sawmill noise and impact, as well as perception of noise on the workers. SPSS version 20 was used for data entry and analysis. The nature of work that is commonly done in sawmills, together with the quantity of woods being worked on generate a lot of noise to the working environments. Noise is hazardous to human health as it can cause increased blood pressure, sleep deprivation and other physiological as well as psychological effects on the workers. The aim of this study was to assess the noise exposure level of sawmill workers to evaluate their safety at work. Three sawmills, all located in Ibadan, Oyo State, South-Western Nigeria were selected for study. Noise level measurements for planning, circular and drilling machines used in the three sawmills were determined using a precision sound pressure tester measurement. The fraction of exposure, and daily personal exposure levels for each of the machines were obtained. Also, questionnaires were administered to obtain subjective responses from the workers on their demographic data, their knowledge about sawmill noise and impact, as well as perception of noise on the workers. SPSS version 20 was used for data entry and analysis.